The Role of Green Promotion in Increasing Purchase Intention: A Systematic Review - Wibowo, Budi; Praja, Arief Kusuma Among; Rahmat Syah, Tantri Yanuar; Dewanto, Heru (Riviera Publishing, 2025)
The purpose of this study is to explore the relationship between green promotion and purchase intention through Systematic Literature Review using the PRISMA method. With public awareness of environmental issues, the company adopts a green promotion strategy to attract interest in environmentally friendly products. The researcher explored 41 articles on the relationship between green promotion and purchase intention from the Scopus database. The results of the study show that the environmental communication base is an important factor in shaping a positive brand perception, influencing purchase intentions, and encouraging consumer loyalty. There are several dominant theories used in this study, Stimulus-Organism-Response and Theory of Planned Behavior, which explain how the external stimulus of green promotion communication with the intention of purchasing products by consumers. In addition, the existence of factors such as advertising credibility, consumer skepticism, and the quality of information in green promotion have a significant effect on purchasing decisions. The implications provide an overview for marketing practitioners in building an effective green marketing communication strategy to attract consumer interest in shopping activities to environmentally friendly products. In addition, it proposes a future research agenda, related to green promotion and purchase intention in the context of sustainable marketing.